Opportunities for harnessing the increased contribution of glacier and snowmelt flows in the Ganges basin - Sharma, Bharat R.; Condappa, D. de (IWA Publishing, 2013)
The topography of the Ganges basin is highly variable, with the steep mountainous region of the Himalaya upstream and the large fertile plains in eastern India and Bangladesh downstream. The contribution from the glaciers to streamflows is supposed to be significant but there is uncertainty surrounding the impact of climate change on glaciers. An application of the Water Evaluation and Planning model was set up which contained an experimental glaciers module. The model also examined the possible impacts of an increase in temperature. The contribution from glaciated areas is significant (60-75%) in the Upper Ganges but reduces downstream, falling to about 19% at Farakka. Climate change-induced rise in temperature logically increases the quantity of snow and ice that melts in glaciated areas. However, this impact decreases from upstream (2?8% to 2?26% at Tehri dam) to downstream (2?1% to 2?4% at Farakka). Such increases in streamflows may create flood events more frequently, or of higher magnitude, in the upper reaches. Potential strategies to exploit this additional water may include the construction of new dams/reservoir storage and the development of groundwater in the basin through managed aquifer recharge. The riparian states of India, Nepal and Bangladesh could harness this opportunity to alleviate physical water scarcity and improve productivity.